2023
DOI: 10.3390/polym15071708
|View full text |Cite
|
Sign up to set email alerts
|

Tension and Compression Properties of 3D-Printed Composites: Print Orientation and Strain Rate Effects

Abstract: This study examines the impact of three factors on the tensile and compressive behaviour of 3D-printed parts: (1) the addition of short carbon fibres to the nylon filament used for 3D printing, (2) the infill pattern, and (3) the speed at which the materials are strained during testing. The results show that adding carbon fibres to the nylon filament reduces variability between tests and emphasises the effect of print orientation. When the infill pattern is aligned with the direction of loading, the tensile st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Nylon White is a stronger and stiffer material by comparison with the conventional nylon used for 3D printers. Fisher et al [44] obtained the elastic tension and compression properties of Nylon White at different strain rates by also considering three different infill parameters including the on-edge orientation used in this study. The material properties of the constituents used in this study are shown in Table 2.…”
Section: Am Methods and Composite Curved Beamsmentioning
confidence: 99%
“…Nylon White is a stronger and stiffer material by comparison with the conventional nylon used for 3D printers. Fisher et al [44] obtained the elastic tension and compression properties of Nylon White at different strain rates by also considering three different infill parameters including the on-edge orientation used in this study. The material properties of the constituents used in this study are shown in Table 2.…”
Section: Am Methods and Composite Curved Beamsmentioning
confidence: 99%
“…One of the most used fibre-reinforced composite filaments in functional 3D printing is the chopped glass or carbon fibre-reinforced nylon filaments due to their mechanical, chemical, and thermal properties [ 14 ]. Research on the effect of the infill of such materials can already be found [ 15 , 16 , 17 , 18 ], mainly due to the fact that the orientation of fibres inside the nylon should contribute to its mechanical properties significantly, and the most investigated mechanical properties are the tensile and compressive strengths of the samples, which is quite strange considering the fact that fibre reinforcement is commonly used to enhance materials’ flexural strength. However, these studies are quite limited in their scope and do not investigate other important parameters, and the choice of other parameters is hardly stated, and often when they are stated, they seem to be chosen randomly or are the factory presets, which should be modified based on a number of factors.…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors applied unconventional deposition strategies, based on a deposition of contour beads only, and a second manufacturing step to obtain such specimens. Fisher et al [10] characterized the longitudinal tensile properties of SCFR-PA6 by testing FFF-ed ASTM D638 [11] standard-complaint dog bone specimens in two configurations: flat specimens, where their gauge length consisted of contour beads only (all parallel to the loading direction), and on-edge 0 • UD specimens, which consisted of all contour beads. Nevertheless, both specimens experienced defect-induced premature failure.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, both specimens experienced defect-induced premature failure. SCFR-PA6 prism-shaped compression specimens were FFF-ed and tested in accordance with the ASTM D695 [12] standard by Fisher et al [10]. To estimate the transversal isotropic material compressive properties, such specimens were printed by contour beads only in the two following orientations: all the beads of a layer being either parallel or perpendicular with the loading direction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation